Muestra de Arte Joven 1988. (Madrid : Instituto de la Juventud, 1988)
Alvarez Basso, Dario ; Cerda, Pepe ; Comajoan, Josep ; Garcia, Dora ; Gimeno, Tomas ; Gomez Bueno, Antonio ; Gonzalez Guerrero, Jose M. ; Herguera, Isabel ; Martin Edo ; Jose M. ; Mayol, Mariano ; etc.
Muestra de Arte Joven 1988, Instituto de la Juventud, Madrid, 1988
boek